Delayed surgery for acute severe colitis is associated with increased risk of postoperative complications. - Randall, J; Singh, B; Warren, B; Travis, S; Mortensen, N; George, B (2010)
BACKGROUND: This study determined the long-term outcome after colectomy for acute severe ulcerative colitis (ASUC) and assessed whether the duration of in-hospital medical therapy is related to postoperative outcome. METHODS: All patients who underwent urgent colectomy and ileostomy for ASUC between 1994 and 2000 were identified from a prospective database. Patient details, preoperative therapy and complications to last follow-up were recorded. RESULTS: Eighty patients were identified, who were treated with intravenous steroids for a median of 6 (range 1-22) days before surgery. Twenty-three (29 per cent) also received intravenous ciclosporin. There were 23 complications in 22 patients in the initial postoperative period. Sixty-eight patients underwent further planned surgery, including restorative ileal pouch-anal anastomosis in 57. During a median follow-up of 5.4 (range 0.5-9.0) years, 48 patients (60 per cent) developed at least one complication. Patients with a major complication at any time during follow-up had a significantly longer duration of medical therapy before colectomy than patients with no major complications (median 8 versus 5 days; P = 0.036). CONCLUSION: Delayed surgery for patients with ASUC who do not respond to medical therapy is associated with an increased risk of postoperative complications.